ENHANCING THE EFFICIENCY OF IRAN KHODRO PERSONNEL THROUGH MODELLING THEIR IN-SERVICE TRAINING - Eftekhari, Ramin; Razavi, S. Ehsan; Fariborzi, Elham (Gênero & Direito, 2019)
Today, authorities of organizations must contemplate the success and status of their units. An alternative to increasing the scientific growth of organizations is to provide in-service educational courses for the personnel. The current research aimed to present a model to improve the quality of the in-service training of Iran Khodro personnel. This was an applied research in terms of the objectives and descriptive-exploratory in terms of the methodology. Based on the theoretical framework of the research, organizational, individual, and educational factors were considered as the influential factors in improving the quality of in-service training for Iran Khodro personnel. A questionnaire was applied to explain the model and collect the required data. The sample size was determined using the Cochran’s formula, and the subjects were selected via simple random sampling. Data analysis was performed in SPSS and LISREL using descriptive and inferential statistics (confirmatory and exploratory factor analysis). According to the results of the descriptive statistics, the mean quality of in-service training and organizational, individual, and educational factors were estimated at 3.83, 3.74, 3.66, and 3.45, respectively. According to the inferential statistics using factor analysis, the obtained results indicated that the response categories raised in the research tool were organizational, individual, and educational factors. As such, the model was developed to improve the quality of the in-service training of Iran Khodro Personnel based on the mentioned factors.